Tax Policy Tools of Selected European Countries as A Mechanism for Counteracting the Effects of The Crisis Caused by the COVID-19 Disease Pandemic - Piotr KASPRZAK; Jerzy FRANKOWSKI (Communications of International Proceedings, 2021)
Crises play an important role in a economics life. They are common and it is impossible to omit them. This following study investigates the concept of ‘crisis’ in the context of economic situation. This text describes the most important financial crises that took place in the past. After that authors passes on a detailed analysis of the actual corona-crisis and the way that it affects the economy globally. The main goal of this study is to show the European state governments reactions  and action to this unusual crisis that were made in the context of tax regulations. In conclusion the target was reached what resulted in this study.
Keywords: Crisis; Corona-Crisis; World Economy; Management; Tax Regulations; Tax Relief